Iktikaf dalam Keadaan Tidak Berpuasa Studi Komparatif Mazhab Maliki dan Mazhab Syafii (AL-FIKRAH: Jurnal Kajian Islam, 2025)
The purpose of this research is to analyze the views of the Maliki and Shafi’i schools regarding the law of i’tikaf without fasting, and to identify the opinion considered the strongest among the two. This research uses a qualitative method through a library research approach, by examining classical fiqh sources from both schools of thought. The research results show that the Maliki school requires fasting in the practice of i'tikaf, whereas the Shafi'i school does not require fasting. However, based on analysis and Islamic legal principles, the opinion that iktikaf is valid without fasting is considered stronger because there is no text that mandates fasting as a condition for the validity of iktikaf. This research provides flexibility in contemporary iktikaf practices, especially for individuals who are unable to fast due to valid excuses or certain conditions. This results of this research are expected to serve as a reference in formulating fatwas and worship guidelines that align with the teachings and dynamics of contemporary society.